Healthcare utilization in general practice before and after psychological treatment: A follow-up data linkage study in primary care. (September 2014) - Prins, Marijn A.; Verhaak, Peter F.M.; Smit, Dineke; Verheij, Robert A.
Abstract Objective. Literature suggests that serious mental health problems increase the use of health services and psychological interventions can reduce this effect. This study investigates whether this effect is also found in primary care patients with less serious mental health problems. Design/setting. Routine electronic health records (EHR) from a representative sample of 128 general practices were linked to patient files from 150 primary care psychologists participating in the NIVEL Primary Care Database, using a trusted third party. Data were linked using the date of birth, gender, and postcode. This yielded 503 unique data pairs that were listed in one of the participating GP practices in 2008–2010, for people who had psychological treatment from a psychologist that ended in 2009. Main outcome measures. The number of contacts, health problems presented, and prescribed medication in general practice were analysed before and after the psychological treatment. Results. Nearly all 503 patients consulted their GP during the six months preceding the psychological treatment (90.9%) and also in the six months after this treatment had ended (83.7%). The frequency of contacts was significantly higher before than after the psychological treatment (6.1 vs. 4.8). Fewer patients contacted their GPs specifically for psychological or social problems (46.3% vs. 38.8%) and fewer patients had anxiolytic drug prescriptions (15.5% vs. 7.6%) after psychological treatment. Conclusion. After psychological treatment, patients contact their GPs less often and present fewer psychological or social problems. Although contact rates seem to decrease, clients of psychologists are still frequent GP attenders.